SUFI MODERN DALAM IMPLEMENTASI AKHLAK DIGITAL - H. Abdul Hakim; Abdul Sani (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
The contemporary digital revolution has transformed the way people communicate and interact on social media. This convenience offers many benefits, but it also raises various problems, such as the spread of fake news, hate speech, cyberbullying, and a decline in ethical communication. Therefore, moral values ​​are needed to guide the wise use of digital media. This study aims to examine the relevance of Sufism values ​​(Sufi behavior) in the Digital Moral Manifesto as an effort to shape more ethical societal behavior in the digital space. The study used a library research method by reviewing various books, scientific journals, and documents of the Digital Moral Manifesto. The results of the study indicate that Sufism values ​​such as sincerity, patience, muraqabah, muhasabah, tawakal, and asceticism are closely related to the principles of digital morality. These values ​​can serve as a foundation for building self-awareness, controlling emotions, guarding one's words on social media, and using technology responsibly. Thus, Sufism plays a crucial role in strengthening the character of society, enabling it to face the challenges of digital life more wisely and with civilized social ethics.